Práticas de gestão de pessoas: uma análise das melhores cooperativas para trabalhar - França, Henrique de Lima Melo; Bressa, Laurine; Estivalete, Vania de Fátima Barros; Ramadam, Amanda Oliveira; Gomes, Tarízi Cioccari (Revista de Gestão e Organizações Cooperativas, 2020)
The present study had the objective of identifying the main practices of people management adopted by the best cooperatives to work, according to a ranking of the magazine Você S/A of 2017. In order to meet the objective, a descriptive and qualitative and quantitative research was carried out. The data collection was based on documentary analysis, through the consultation of the magazine Você S/A with the Best Companies to Work in 2017, as well as access to the website and the sustainability and management reports for the year 2017 of the cooperatives. It can be noticed that the 16 cooperatives awarded belong to two branches, credit and health. With regard to people management practices, the two cooperatives have established practices. In the credit sector, there was greater expressiveness in endomarketing and training and development. While in the health sector, the most significant factors were, social benefits and T&D.